The level of reliability of the four (full outline of unresponsiveness) score in assessing the level of consciousness of stroke patients - Dwi Wiyono; Yulian Wiji Utami; Dina Dewi Sartika Lestari Ismail (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Similarly to the Glasgow Coma Scale (GCS), the FOUR score can evaluate the level of awareness in stroke patients. This research aimed to evaluate the accuracy of using the FOUR score instrument to the more commonly used GCS method for determining a patient's degree of consciousness in the ER following a stroke. This research method is an analytic observational study with a total of 102 samples, namely stroke patients in the emergency room of RSUD dr. Soehadi prijonegoro Sragen Regency. The process of collecting research data was carried out by three enumerators to see the level of reliability using instruments in the form of awareness assessment observation sheets and standard FOUR score operational procedures. The study found that the FOUR score instrument had a total reliability of 0.830 as measured by the Intraclass Correlation Coefficient (ICC) test, whereas the GCS reliability was 0.864. This study found that the FOUR score and GCS were reliable in determining whether or not a stroke patient was conscious. This finding can be understood to mean that there was no discrepancy in the three evaluators' assessments of consciousness when using the FOUR score or GCS. This study recommends that follow-up needs to be done to find the sensitivity and specificity values of the FOUR score instrument as an instrument for assessing the awareness of stroke patients.Abstrak: Sama halnya dengan Glasgow Coma Scale (GCS), FOUR score dapat mengevaluasi tingkat kesadaran pada pasien stroke. Tujuan dari penelitian ini adalah untuk mengevaluasi akurasi penggunaan instrumen FOUR score  dengan metode GCS yang lebih umum digunakan untuk menentukan derajat kesadaran pasien di UGD setelah stroke. Metode penelitian ini merupakan penelitian observasi analitik dengan jumlah sampel sebanyak 102 orang yaitu pasien stroke di IGD RSUD dr. Soehadi prijonegoro Kabupaten Sragen. Proses pengambilan data penelitian dilakukan oleh tiga orang enumerator untuk melihat tingkat reliabilitasnya dengan menggunakan instrumen berupa lembar observasi pengkajian kesadaran dan standar prosedur operasional FOUR score. Hasil penelitian ini diperoleh tingkat reliabilitas total instrumen FOUR score menggunakan uji Intraclass Correlation Coefficient (ICC) sebesar 0,830, sedangkan pada GCS sebesar 0,864. Kesimpulan dari penelitian ini adalah FOUR score dan GCS memiliki tingkat reliabilitas yang baik dalam menilai tingkat kesadaran pada pasien stroke sehingga dapat diartikan juga di antara ketiga enumerator tidak ada perbedaan persepsi dalam melakukan penilaian kesadaran baik menggunakan instrumen FOUR score maupun metode GCS. Rekomendasi penelitian ini adalah perlu dilakukan tindak lanjut untuk mencari nilai sensitivitas dan spesifisitas dari instrumen FOUR score sebagai instrumen penilaian kesadaran pasien stroke.